N′-(5-Bromo-2-hydroxybenzylidene)-4-methylbenzohydrazide - Yang, De-Suo (International Union of Crystallography, 2011)
The molecule of the title compound, C(15)H(13)BrN(2)O(2), displays an E conformation with respect to the C=N double bond and the dihedral angle between the planes of the benzene rings is 3.1 (2)°. An intramolecular O—H⋯N interaction generates an S(6) ring. In the crystal, molecules are linked by N—H⋯O hydrogen bonds, forming C(4) chains along the c-axis direction.